Kolaborasi Digital Dan Entrepreneurial Marketing Guna Peningkatan Daya Saing Dan Kinerja Bisnis UMKM Makanan Di Kota Semarang - Ýanti Pujiastuti; Pantawis, Setyo (Jurnal Ilmiah Ekonomi Islam, 2025)
The fundamental problems in efforts to develop MSME businesses is the low adoption of MSME technology. This has an impact on the competitiveness of MSME businesses becoming increasingly reduced and leading to a decline in business performance. This is contradictory where the development of IT should open up wide opportunities for MSMEs in developing their competitiveness as well as their business performance. However, MSMEs in general do not understand the existence of this very potential opportunity. In fact, the characteristics of MSME business excellence, have high flexibility to manage their business, considering that in general the resources owned by MSMEs are not too large and not complex.and research results. This study aims to test the collaboration of digital marketing and entrepreneurial marketing that can create marketing innovation. The implementation of digital and entrepreneurial marketing will increase consumer accessibility to obtain products, make it easier for consumers to make payments and access information and services provided. These various aspects will increase the value of MSME products, thereby creating persuasion for potential consumers and expanding market coverage. The research method is quantitative with the distribution of questionnaires to obtain primary data which is then analyzed using the PLS program. The population of food UMKM actors in Semarang City with a sample size using the Lemeshow formula using cluster sampling. The results of the study found the influence of entrepreneurial marketing and digital marketing on innovative marketing and subsequently improved marketing performance. The importance of integrating entrepreneurial marketing and digital marketing as a strategy to increase innovation in marketing and, ultimately, the company's marketing performance. Companies that are able to combine these two approaches will be better able to adapt to market changes and meet the evolving needs of customers